Development of Digital Comic as Learning Media on Immune System Topic in SMAN 13 Jakarta - Nurinayati, Fitri; Sartono, Nurmasari; Evriyani, Dian (Biosfer: Jurnal Pendidikan Biologi, 2014)
Comics are popular among teenagers in which senior high school students included. One type of comics, digital comic, has recently become a global trend, which beneficial to be utilized as an effective learning media. In order to take benefits from this great opportunity, this research was aimed to develop a digital comic on immune system topic. This study was conducted at SMAN 13 Jakarta using research and development method. Samples were consisted of students and biology teacher class XI, media expert, and material expert. A total of six steps proceeded including need assesment, objective formulation, material development, instruments development, media development, and try-out and revision. During the try out test, all samples were involved as users. The product received a very good interpretation from all samples with feasibility ranged from 81,3-90,9%. This result implied that this digital comic was qualified as learning media on immune system topic for class XI.